Development of lightweight aggregate mortar skin layer for an innovative sandwich concrete composite - Mo, Kim Hung; Hussin, Muhammad Nadzmi; Ling, Tung Chai; Ramli Sulong, Nor Hafizah; Lee, Foo Wei; Yuen, Choon Wah (Elsevier, 2020)
This research strives to develop a high-temperature resistant lightweight aggregate (LWA) mortar skin layer for use in sandwich concrete composite. The first phase of the research was focused on the development of the LWA mortar while the subsequent phase of work dealt with assessing the performance of the resulting sandwich concrete composite. In phase 1 of the investigation, it was found that mortar incorporating calcium aluminate cement (CAC) as binder and lightweight expanded clay aggregate (LECA) as fine aggregate had the best resistance towards high temperature of 1000 °C. The developed mortar along with basalt fibre mesh were used to form textile reinforced concrete (TRC) as skin layer which could still exhibit residual strength upon heated to high temperature. Furthermore, sandwich composite beam made of the TRC skin and aerated concrete as core had better flexural strength/weight ratio compared to that using conventional EPS foam as the core material. There was also no significant damage found on the sandwich concrete composite upon exposure to direct flame. The findings suggest that the development of the sandwich concrete composite is promising and further works can be explored to improve the performance. © 2019 Elsevier Ltd